Branched Chain Amino Acids, New Target of Germinated Brown Rice against Type 2 Diabetes Mellitus: A Randomized Controlled Trial. Issue 4 (26th January 2023) - Wan, Wenting; Jiang, Xianchen; Zhao, Ruifang; Cai, Fenfen; Wu, Fan; Hu, Yunqi; Zhou, Xiaoqin; Liu, Zhipeng; Shan, Yujuan
Abstract : Scope: Adequate intake of whole grain foods is beneficial to type 2 diabetes mellitus (T2DM). Whether the preventive effects are related with metabolism of branched‐chain amino acids (BCAAs) is unclear. The study aims to evaluate the effects of germinated brown rice (GBR) intervention on BCAAs metabolism in T2DM patients. Methods and results: In this randomized controlled trial, subjects with T2DM are instructed to consume 100 g day −1 GBR (GBR group, n =42) or equal staple food (Control group, n =25) for 3 months. Food frequency questionnaires (FFQ) and serum samples are collected before and after the intervention. In the GBR group, fasting blood glucose (FBG), fasting insulin (FINS), and serum BCAAs are decreased, and islet function is improved ( p <0.05). Logistic regression analysis showed that FBG (odds ratios [OR]: 1.55, 95% confidence interval [CI]: 1.01–1.84) and energy (OR: 1.21, 95% CI: 1.09–1.30) are positively associated with serum total BCAAs level, while FINS is negatively associated (OR: 0.20, 95% CI: 0.04–0.88). Simultaneously, the key enzymes of BCAAs decomposition, which promotes glycolysis by activating pyruvate dehydrogenase (PDH), are significantly increased. Conclusion: GBR improves the indicators of T2DM patients, and the underlying mechanisms include improving insulin resistance and accelerating catabolism of BCAAs. Abstract : Germinated brown rice (GBR) improves type 2 diabetes mellitus (T2DM), and the underlying mechanisms include improving insulin resistance and accelerating catabolism of branched‐chain amino acids (BCAAs).